2019
DOI: 10.1002/aenm.201803948
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic PCBM:Dimer Population in Solar Cells under Light and Temperature Fluctuations

Abstract: polymers and device architectures are steadily increasing the performance of polymer:fullerene OSCs. [3][4][5] Evidently, the competitiveness of this technology is predicated on the achievement of longterm stability, required for practical utilization. The loss of PCE over time can be attributed to numerous stress factors. Environmental elements such as oxygen and humidity exposure can adversely affect performance, as well as mechanical failure, and robust encapsulation, mechanical, and interfacial design are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 41 publications
1
26
1
Order By: Relevance
“…5(d). 8,79,99 While fullerene dimerisation generally dominates under environmentally relevant operating conditions, significant decrease of the fullerene dimer population can occur with increasing temperature, where the morphological stabilisation effect of fullerene dimerisation can be reversed.…”
Section: Morphological Stability Under Thermal Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…5(d). 8,79,99 While fullerene dimerisation generally dominates under environmentally relevant operating conditions, significant decrease of the fullerene dimer population can occur with increasing temperature, where the morphological stabilisation effect of fullerene dimerisation can be reversed.…”
Section: Morphological Stability Under Thermal Stressmentioning
confidence: 99%
“…(c) The PC 61 BM monomer and PC 61 BM dimer populations in OSC systems with different polymer:PC 61 BM (1:2) blend systems are shown with (left) increasing radiant exposure and (right) with increasing annealing temperature for prior irradiated PCDTBT:PC 61 BM (1:2) blend films. The ''2+2'' cycloaddition dimerisation process (see schematic in (c)) is reversible, significant dimer population decrease is observed above 80 • C. 8,79 (d) A minimal model built to predict the dynamic PC 61 BM monomer:dimer populations under simultaneous and fluctuating light and thermal stress exposure associated with in operando conditions 79. Reproduced with permission [79].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The kinetics of dimer formation and decomposition depend on temperature, light irradiation dose, and blend composition. [ 127 ] The activation energy for photodimerization is estimated to be 0.021 eV, which is considerably smaller than that for decomposition (0.96 eV), consistent with decomposition occurring at elevated temperatures. PCBM dimerization results in widening of the bandgap, which in turn results in increased disorder of both the HOMO and the LUMO level of PCBM.…”
Section: Stability Issues Of Opvsmentioning
confidence: 89%
“…These topo-chemical considerations explain the smaller chain lengths obtained for these fullerenes as well as the reaction's suppression at lower temperatures 12 . Heumüller et al 17 and Pont et al 18 have investigated the role of polymers in determining the dimerization rate and fraction of PC 61 BM undergoing dimerization in BHJs. They concluded that PC 61 BM crystallinity and PC 61 BM exciton quenching time dictate the reaction kinetics.…”
mentioning
confidence: 99%